Hubungan Tingkat Kepatuhan Konsumsi Formula 100 dengan Kenaikan Berat Badan Balita Gizi Buruk di Rumah Gizi Kota Semarang: The Relationship of Formula 100 Consumption Compliance Level to Weight Gain of Malnutrition Toddlers at the Rumah Gizi Semarang City - Anggita, Reni Dwi; Fatimah, Siti; Asna, Alfi Fairuz (Universitas Airlangga, 2025)
Background: In 2023, 49 cases of toddler malnutrition were reported in Semarang City. Malnutrition management is an approach to enhance the nutritional status of infants and toddlers under five. The administration of Formula 100 is a strategy implemented by the Semarang City Health Office to promote weight gain among malnourished toddlers in order to catch up on their weight and achieve normal weight relative to their length or height. Objectives: This study aims to determine the relationship between compliance with Formula 100 consumption and weight gain in malnourished toddlers at Rumah Gizi in Semarang City. Methods: This study employed a quasi-experimental method with a one-group pretest-posttest design. The subjects were 26 toddlers or the total population of malnourished toddlers at Rumah Gizi. Data were analyzed using Spearman’s rank correlation, Pearson’s product-moment correlation, and the chi-squared test. Results: Univariate analysis demonstrated that 88.5% of toddlers consumed Formula 100 as prescribed for 35 days. Adequacy levels for energy (7.7%), protein (3.8%), fat (3.8%) and carbohydrate (26.9%) were categorized as good, and 57.7% of toddlers did not experience infectious diseases. No relationship was found between compliance with Formula 100 consumption (p-value=0.075) as well as adequacy levels for energy (p-value=0.869), protein (p-value=0.609), fat (p-value=0.691), and carbohydrate (p-value=0.787) and weight gain in malnourished toddlers at Rumah Gizi in Semarang City (p-value>0.05). However, a relationship was found between infectious diseases and weight gain (p-value=0.047). Conclusions: Compliance with Formula 100 consumption was not associated with weight gain in malnourished toddlers at Rumah Gizi in Semarang City.